2016
DOI: 10.1016/j.marpolbul.2016.06.095
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient distribution and structure affect the acidification of eutrophic ocean margins: A case study in southwestern coast of the Laizhou Bay, China

Abstract: The effects of nutrient distribution and structure on the acidity of coastal waters were analyzed based on the data of 48 surface water samples collected in the southwestern coast of the Laizhou Bay and its adjacent rivers (SWLZB) which are heavily influenced by nutrient-laden discharges. The concentration and structure of nutrients varied considerably along the coast owing to different contributors. The studied inshore waters exhibited a sign of acidification. The pH was significantly negatively correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The total annual flux of DIN into Jiaozhou Bay from XQ was 59.0 Mmol N, as calculated by the data provided by the Chinese Ocean Environmental Quality Bulletin in 2012. The DIN fluxes from JL were estimated to be approximately one-fifth of XQ, according to the nutrient concentration and flow discharge ratio data for the two rivers (Zhang and Gao 2016;Zhang et al 2012). Thus, the denitrification and anammox both achieved 16.1% removal of the annual flux of the total nitrogen in XQ and JL.…”
Section: Discussionmentioning
confidence: 99%
“…The total annual flux of DIN into Jiaozhou Bay from XQ was 59.0 Mmol N, as calculated by the data provided by the Chinese Ocean Environmental Quality Bulletin in 2012. The DIN fluxes from JL were estimated to be approximately one-fifth of XQ, according to the nutrient concentration and flow discharge ratio data for the two rivers (Zhang and Gao 2016;Zhang et al 2012). Thus, the denitrification and anammox both achieved 16.1% removal of the annual flux of the total nitrogen in XQ and JL.…”
Section: Discussionmentioning
confidence: 99%
“…Ocean warming and increased stratification decrease the oxygen content of the ocean (Griffiths et al, 2017;Schmidtko et al, 2017;Bindoff et al, 2019), lead to an expansion of oxygen minimum zones in the open ocean (Stramma et al, 2012;Zhang et al, 2013) and exacerbate the creation of anoxic 'dead zones' in the coastal oceans (Breitburg et al, 2018). Such a decline (characterized by successive dissolved oxygen concentration thresholds) could affect a wide range of marine organisms and reduce marine habitats (Chan et al, 2008;Vaquer-Sunyer and Duarte, 2008;Hoegh-Guldberg and Bruno, 2010;Altieri and Gedan, 2015;Breitburg et al, 2018) and can also lead to further local acidification (Zhang and Gao, 2016;Laurent et al, 2017).…”
Section: Oceanicmentioning
confidence: 99%
“…We collected relevant data from several studies and literature and found that there were relatively abundant measurements in September 2012. The mean values of the sampling sites at the estuaries of the Xiaoqinghe River (K-section, Figure 1) and the Yuhe River (H-section, Figure 1) were set as the concentration at these two estuaries, respectively [24]. The concentration of the sampling site at the tidal portion of the Jiaolaihe River was set [24].…”
Section: Total Nitrogenmentioning
confidence: 99%
“…The mean values of the sampling sites at the estuaries of the Xiaoqinghe River (K-section, Figure 1) and the Yuhe River (H-section, Figure 1) were set as the concentration at these two estuaries, respectively [24]. The concentration of the sampling site at the tidal portion of the Jiaolaihe River was set [24]. The concentration of TN at the Yellow River estuary referred to the sampling station data from the Lijin station in the lower Yellow River [25].…”
Section: Total Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation